Cold, Hot, Lukewarm? ----Exploring the Integration of Transformational Learning and Conceptual Change Theories in Adult Education - Yuan Zhang; Jonathan E. Taylor; Steven B Frye (Adult Education Research Conference, 2025)
As an intellectually stimulating session, this roundtable explores integrating Transformational Learning and Conceptual Change Theories to enhance adult education with new perspectives and strategies for deeper, more effective learning outcomes.
Keywords: transformational learning; conceptual change; adult education